Hypercalcemia in a patient with SLE and antiphospholipid antibody syndrome: a rare case report from Bangladesh - Dewan, G (Journal of Universal College of Medical Sciences, 2014)
Association of hypercalcemia with SLE is very rare. Since initial report in 1991 only hand full cases have been described mainly in adult patients sporadically. Three pattern observed in this rare presentation. Commonly it is associated with serositis and lymphadenopathy or lymphedema known as hypercalcemia-lymphadenopathy SLE {HL-SLE) or hypercalcemia- lymphedema syndrome. Second group do not show this particular association. Concomitant primary hyperparathyroidism is responsible for third variety. This report describes a case of hypercalcemia associated with SLE from Bangladesh. DOI: http://dx.doi.org/10.3126/jucms.v2i1.10490 Journal of Universal College of Medical Sciences (2014) Vol.2(1): 35-37